Can Electronic Monitoring Reduce Reoffending? - Jenny Williams; Don Weatherburn (Institute of Labor Economics (IZA), 2019)
This research evaluates the impact of electronic monitoring as an alternative to prison on reoffending. Leveraging plausibly exogenous variation in sentencing outcomes generated by quasi- random assignment of judges, we find electronic monitoring reduces reoffending within 24 months by 16 percentage points compared to serving a prison sentence. For offenders who are less than 30, the reduction is 43 percentage points, with sizeable and significant reductions in reoffending persisting for 8 years. Our calculations suggest that criminal justice costs are reduced by around 30,000 for each eligible offender who serves their sentence under electronic monitoring rather than in prison.
Keywords: K42; 330; electronic monitoring; prison; reoffending; crime